KONDISI KETAHANAN PANGAN PADA SENTRA PRODUKSI PADI DI PROVINSI RIAU - Ummul Muthmainnah Ulya; Edi Surianto; Tengku Rosmawati; Saripah Ulpah (Indonesian Journal of Agricultural Economics, 2022)
Food security is a condition where the need for food is met for everyone. Aspects food security are safe, equitable and affordable quantity and quality. Food security has 3 important indicators, consists of: (1) food availability, (2) food access and (3) food quality. This study aims to analysis: (1) food availability at rice production centers in Riau Province, (2) food access at rice production centers in Riau Province, and (3) food quality at rice production centers in Riau Province. The research location is in Rokan Hilir, Pelalawan, and Siak Regencies. The research location was chosen purposively, based on rice production centers in Riau Province. The method used is a literature study, using secondary data, in the form of time series data from 2019-2021. Data analysis was carried out with descriptive qualitative and quantitative descriptive, as well as FSQ (Food Security Quotient) analysis. The results showed that overall, the condition of food availability in the rice production centers areas in Riau Province with an FSQ value of 4.432, which is very resistant. On the food access indicator, the FSQ value is 0.846 which means this condition is secure and on the food quality indicator the FSQ value is 2.096, which is very secure.